Decline of genetic variability in a captive population of Pacific white shrimp Penaeus (Litopenaeus) vannamei using microsatellite and pedigree information - Vela-Avitúa, Sergio; Montaldo, Hugo H.; Márquez-Valdelamar, Laura; Campos-Montes, Gabriel R.; Castillo-Juárez, Héctor (Electronic Journal of Biotechnology, 2013)
Background: The objective of this study was to estimate the decline of genetic variability and the changes in effective population size in three shrimp populations. One was a wild population collected at several points in the Mexican Pacific Ocean. The other two populations were different generations (7 and 9) from a captive population selected for growth and survival. Microsatellite markers and pedigree were both used to assess genetic variability and effective population size. Results: Using 26 loci, both captive populations showed a decline in the expected heterozygosity (20%) and allelic diversity indices (48 to 91%) compared to the wild population (P < 0.05). The studied captive populations did not differ significantly from each other regarding their expected heterozygosity or allelic diversity indices (P > 0.05). Effective population size estimates based on microsatellites declined from 48.2 to 64.0% in cultured populations (P < 0.05) compared to the wild population. Conclusions: An important decline of genetic variability in the cultured selected population due to domestication, and evidence of a further smaller decline in effective population size across generations in the selected population were observed when analyzing pedigree (41%) and microsatellite data (37%). Pedigree keeping is required to prevent the decline of effective population size and maintain genetic variability in shrimp breeding programs, while microsatellites are useful to assess effective population size changes at the population level.